2008
DOI: 10.2987/5658.1
|View full text |Cite
|
Sign up to set email alerts
|

A Biodegradable Lethal Ovitrap for Control of Container-Breeding Aedes

Abstract: Lethal ovitraps (LO) have been successfully deployed in dengue control operations in north Queensland, Australia since 2004. However, the current plastic-bucket LO must be retrieved before the pesticide-treated strip degrades and the trap begins producing mosquitoes. The logistics involved with trap retrieval are considerable and include recording trap location and retrieval date onto a database, locating and retrieving each trap, and examining lethal ovitraps for eggs. Collectively, these necessary activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 16 publications
0
36
0
2
Order By: Relevance
“…Nevertheless, field trials using metofluthrin over large contiguous areas are warranted. Registered metofluthrin emanators, in concert with biodegradable lethal ovitraps, 21 could be provided to the public as part of a "do it yourself" community participation dengue control strategy. If metofluthrin emanators were commercially available, media campaigns and websites (e.g., http://www.health.qld.gov.au/ dengue/default.asp ) encouraging their use during an outbreak could be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, field trials using metofluthrin over large contiguous areas are warranted. Registered metofluthrin emanators, in concert with biodegradable lethal ovitraps, 21 could be provided to the public as part of a "do it yourself" community participation dengue control strategy. If metofluthrin emanators were commercially available, media campaigns and websites (e.g., http://www.health.qld.gov.au/ dengue/default.asp ) encouraging their use during an outbreak could be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Novel ovitraps were therefore designed to also target the adult mosquito. These traps include designs such as the ‘sticky’ trap [7,16,17] or ‘double-sticky’ trap [8] in which gravid mosquitoes are captured using glue, or lethal ovitraps [18-20] in which mosquitoes are exposed to insecticides. A major disadvantage of these lethal ovitraps is the fact that insecticides deployed in such traps have shown reduced efficacy due to widespread insecticide resistance in Aedes populations [21].…”
Section: Introductionmentioning
confidence: 99%
“…Perich et al (2003) found reduction of A. aegypti in Brazil, but studies performed in Thailand gave mixed results (Sithiprasasna et al 2003). Different trials in Australia showed an acceptable performance of these LOs but created several additional operational problems which could be solved by using biodegradable ovitraps (Ritchie et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Different devices have been studied and are now commercialized. In some of them, the rough egg-laying wooden paddle was replaced by a velour paper strip treated with an insecticide like deltamethrin or bifenthrin while others added a sticky surface Williams et al 2007;Ritchie et al 2008Ritchie et al , 2009Rapley et al 2009;Chadee and Ritchie 2010). The newest ones make them more attractive to oviposit (Attractant-Bait Lethal Ovitrap ALOT) in which the ovitrap is filled with water laced with attractants and the container is lined with a fabric impregnated with an insecticide to kill the adults when they land to oviposit their eggs (Wesson et al 2012).…”
Section: Introductionmentioning
confidence: 99%